WORD-FORMATIVE MEANING OF ACTION SEMELFACTIVENESS IN THE KHANTY LANGUAGE (AS EXEMPLIFIED IN THE KAZYM DIALECT) - Irina Maksiovna Moldanova (Sovremennye Issledovaniâ Socialʹnyh Problem, 2015)
Study of verb formation holds a high position in the Finno-Ugric linguistics. In spite of works on the verb formation in other dialects of the Khanty language there are many gaps and uncovered issues in description of the Kazym dialect. Goal and tasks of the research. The main goal of the research is to find suffixes with the meaning of action semelfactiveness in the Kazym dialect of the Khanty language, to specify the list of suffixes and the meanings given to the verb. According to the goal stated the following tasks are completed in the work: 1. To collect factual material: verbs with the meaning of semelfactiveness using the sources of literature, colloquial and dialect speech. 2. To analyze and specify morphological characteristic of the semelfactive verbs 3. To detect productivity of the verb suffixes being studied and compare their semantics with other dialects of the Khanty language. Academic novelty. In this work we have examined considerable layer of semelfactive verbs that allows us to specify the meanings of suffixes, detect their productivity. Topicality of this research is explained by the fact that the issue of action semelfactiveness using the example of the Kazym dialect of the Khanty language has not been specially studied.